SOCIAL PROBLEM AND MEDICAL SOLUTION TO UTERINE RUPTURE (World Bulletin of Public Health, 2024)
This article discusses the results of studies of women with uterine ruptures,main causes (scar, drug use, trauma, etc.), pathogenesis. Legal basis for the use of prostaglandins, the “fundal pressure” method. Management algorithm for suspected uterine rupture.